Lighthouse Jetty, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., 2011)
A picture of the Lighthouse Jetty. In this picture you can see the lighthouse and people on the jetty. Also there are boats docked.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Ships--Trinidad and Tobago; Harbors--Trinidad and Tobago; Lighthouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Docks--Trinidad and Tobago; [1910]; Sailing ships--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Ports of entry--Trinidad and Tobago